2016
DOI: 10.1021/acscombsci.5b00197
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Assembly of Spirolactones through NHC-Catalyzed Remote γ-Carbon Addition of Enals with Isatins

Abstract: A chiral N-heterocyclic carbene (NHC)-catalyzed formal [4 + 2] annulation of β-methyl substituted enals with isatins was developed to construct six-membered spirolactones bearing highly congested quaternary carbon stereocentersin good yields and high enantioselectivities. The strategy realized a challenging remote γ-carbon addition of enals and chiral control of β-methyl substituted enals in the presence of the NHC catalyst only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 45 publications
0
9
0
2
Order By: Relevance
“…Typical examples involving NHC-catalyzed azolium dienolates by employing the oxidative γ-functionalization of enals are shown in Scheme 63. [91] In 2013, Chi and coworkers reported that the heteroaryl aldehydes containing an indole, benzofuran or benzothiophene moiety also worked well in this process (Scheme 64 with a trifluoromethyl ketone or isatin to form a polycyclic lactone, which contains a quaternary spirocyclic chiral carbon center. The α-branched aryl aldehydes were employed as suitable substrates and gave the corresponding products in moderate to good yields and high enantioselectivities.…”
Section: Scheme 62 Nhc-catalyzed Oxidative [4+2] Cycloaddition Via DImentioning
confidence: 99%
“…Typical examples involving NHC-catalyzed azolium dienolates by employing the oxidative γ-functionalization of enals are shown in Scheme 63. [91] In 2013, Chi and coworkers reported that the heteroaryl aldehydes containing an indole, benzofuran or benzothiophene moiety also worked well in this process (Scheme 64 with a trifluoromethyl ketone or isatin to form a polycyclic lactone, which contains a quaternary spirocyclic chiral carbon center. The α-branched aryl aldehydes were employed as suitable substrates and gave the corresponding products in moderate to good yields and high enantioselectivities.…”
Section: Scheme 62 Nhc-catalyzed Oxidative [4+2] Cycloaddition Via DImentioning
confidence: 99%
“…Durch weitere Untersuchungen zur oxidativen Bildung der Spezies VI fanden Liu et al., dass die NHC‐Vorstufe C‐4 ein effizienter Promotor der [4+2]‐Cycloaddition von 13 mit 11 ist (Schema ) . Für die Bildung entsprechender Cycloaddukte 12 , ohne die Verwendung von Lewis‐ oder Brønsted‐Säuren als Cokatalysatoren, wurden gute Ausbeuten und hohe Enantioselektivitäten erzielt.…”
Section: [4+2]‐cycloadditionen Von Carbonylverbindungenunclassified
“…2011 年, You 课题组 [38] 2016 年, 我们课题组 [59] 通过以 α,β-不饱和醛 105 为 底物, 在 NHC、碳酸铯和氧化剂催化体系中实现了 γ 位 的 sp 3 碳活化, 进一步与靛红 104 反应构建出一系列螺 内酯类化合物 106 (Scheme 10). 与 Ye 等 [57] 利用酰氯实 在之前工作的基础上, Chi 课题组 [60]…”
Section: 羰基化合物 β-碳参与的反应unclassified